1999
DOI: 10.1118/1.598527
|View full text |Cite
|
Sign up to set email alerts
|

Boron neutron capture synovectomy: Treatment of rheumatoid arthritis based on the nuclear reaction

Abstract: A novel application of the 10 B(n,␣) 7 Li nuclear reaction for the treatment of rheumatoid arthritis is under investigation. Rheumatoid arthritis is characterized by a painful inflammation of the membrane ͑synovium͒ lining articular joints. Since the tissue targeted for treatment is the diseased synovial membrane and the goal is synovial ablation ͑''synovectomy''͒, the proposed treatment is called Boron Neutron Capture Synovectomy. Development of this therapeutic modality has been carried out in a number of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This has been confirmed by previous dissection studies involving several different compounds (Binello 1999). Therefore, in the simulation study described here, 10 B is assumed to exist only in the synovium and/or the synovial fluid.…”
Section: Proposed Experimental Approachmentioning
confidence: 49%
See 4 more Smart Citations
“…This has been confirmed by previous dissection studies involving several different compounds (Binello 1999). Therefore, in the simulation study described here, 10 B is assumed to exist only in the synovium and/or the synovial fluid.…”
Section: Proposed Experimental Approachmentioning
confidence: 49%
“…Dissection studies showed that some compounds, such as boron metal particulate, coagulate in the synovial fluid and do not disperse to other regions within the joint even after 24 hours; some others, such as the K 2 B 12 H 12 , redistribute throughout the knee quickly and leave the joint within 60 minutes (Binello 1999). If the information regarding the compound redistribution time course could be determined using an in vivo 10 B mapping technique performed on a single living animal, it would allow rejection of some compounds at the screening phase, leaving only those with reasonable longevity and distribution characteristics for more costly and time-consuming dissection studies.…”
Section: Technology Research Reactor (Mitr)mentioning
confidence: 99%
See 3 more Smart Citations